Three-Finger α-Neurotoxins and the Nicotinic Acetylcholine Receptor, Forty Years On - Selvanayagam Nirthanan; Matthew C.E. Gwee (Elsevier, 2004)
The discovery, about forty years ago, of α-bungarotoxin, a three-finger α-neurotoxin from Bungarus multicinctus venom, enabled the isolation of the nicotinic acetylcholine receptor (nAChR), making it one of the most thoroughly characterized receptors today. Since then, the sites of interaction between α-neurotoxins and nAChRs have largely been delineated, revealing the remarkable plasticity of the three-finger toxin fold that has optimally evolved to utilize different combinations of functional groups to generate a panoply of target specificities to discern subtle differences between nAChR subtypes. New facets in toxinology have now broadened the scope for the use of α-neurotoxins in scientific discovery. For instance, the development of short, combinatorial library-derived, synthetic peptides that bind with sub-nanomolar affinity to α-bungarotoxin and prevent its interaction with muscle nAChRs has led to the in vivo neutralization of experimental α-bungarotoxin envenomation, while the successful introduction of pharmatopes bearing "α-bungarotoxin-sensitive sites" into toxin-insensitive nAChRs has permitted the use of various α-neurotoxin tags to localize and characterize new receptor subtypes. More ambitious strategies can now be envisaged for engineering rationally designed novel activities on three-finger toxin scaffolds to generate lead peptides of therapeutic value that target the nicotinic pharmacopoeia. This review details the progress made towards achieving this goal. Keywords:: nicotinic acetylcholine receptor, α-neurotoxin, three-finger toxin, neuromuscular block, pharmacological probe